Assessment of mathematical models of drying of jabuticaba peels through performance indicators - Soares, Dayane Santos Conceição; Santos, Jéssica Teles Sirqueira; Lima, Lucas Almeida Leite Costa; Nunes, Tatiana Pacheco; Oliveira Júnior, Antonio Martins (Scientia Plena, 2016)
Brazil is a country with a huge diversity of native fruits, and one of them is jabuticaba. The jabuticaba peel is the main part of the fruit due to the high level of bioactive compounds besides fibers and minerals. Therefore, it is necessary to use this residue that can be reused for several purposes, such as extraction of natural colouring. Drying technology is applied with the objective of increasing the shelf life of the jabuticaba skin which has a high level of water. In the present work, an evaluation of mathematical drying models through performance indicators which were accuracy factor (Af), bias factor (Bf), root mean square error (RMSE) and standard error of prediction (%SEP) was done for studying the drying kinetic of the jabuticaba pell. The drying process was conducted in a convective tray dryer at 43 ⁰C for 352 min. According to the results, the two terms model and the Midilli model were the ones that better fitted the experimental data, and the Page model was the third one. However, the convenience of using the Page model is due to the computational and numerical advantage because it is needed to estimate only two parameters.